Cost and Return Analysis of Tomato Cultivation in Haryana (Indian Journal of Extension Education, 2023)
The study was carried out in Yamuna Nagar, Kurukshetra, and Karnal districts of Haryana during 2021-22. A total of 210 tomato growers were interviewed to collect data to study the thorough cost and return analysis of tomato cultivation. Tomato cultivation was a profitable venture for farmers with a BC ratio of 1: 1.86. The per hectare cost of cultivation was worked out to be Rs. 305701.14 of which major contributors were rental value of land (24.96%), picking/harvesting charges (15.44%), transportation (11.61%) and nursery raising/seed (5.74%). The gross return, return over variable cost and net return per hectare were Rs. 569528.28, 412210.72, and 263827.14 on an overall basis. The production cost per quintal of tomato was computed to be Rs. 707.23 per quintal. It was suggested that farmers should take tomato cultivation with a business and market-oriented approach to compete with the challenges of the glut situation and opt cooperative approach in the production and selling of crops to avail maximum profit by reducing the cost of inputs and transportation and ultimately improving bargaining and negotiating power for better price availing.